Relationship between Obesity and Dental Caries in Some University Students: A Pilot Study - Soo-Jeong Hwang; Hoon Kim; Min-Seock Seo (The Korean Society of Dental Hygiene Science, 2021)
Background: Obesity and dental caries have common risk factors such as food intake, eating habits, and lifestyle. Nevertheless, there has been no consensus on the significant association between obesity and dental caries, and additional studies are needed. We investigated the relationship between obesity and dental caries in some college students in this pilot study.Methods: Forty-two obese college students (body mass index [BMI]≥25) registered at a University Obesity Clinic and 19 normal students (18.5≤BMI＜25) were recruited. Oral examinations were conducted, and anthropometric data and blood samples were collected. The blood concentrations of low-density lipoprotein (LDL), high-density lipoprotein, and triglyceride were also measured. After controlling for dental plaque index, a univariate analysis of dental caries indicators related to obesity was performed; partial correlation analysis was also conducted. A nonparametric test was used for the analysis of gender-related trends due to the limited number of participants.Results: The obese group had significantly fewer missing teeth (p=0.014), missing surfaces (p=0.035), filled surfaces (p=0.038), and decayed-missing-filled surfaces (p=0.020) than the normal group. There was no difference between the males in the normal and obese groups. The females in the obese group had significantly fewer missing teeth (p=0.003), missing surfaces (p=0.003), and decayed-missing-filled surfaces (p=0.046). Partial correlation analysis showed a weak negative correlation (r=−0.256) between the blood LDL concentration and decayed-missing-filled teeth. The other obesity and dental caries indicators were not correlated.Conclusion:The blood cholesterol concentration had a negative relationship with dental caries, and there were fewer cases of dental caries in the obese group in this study. However, it is important to clarify the relationship between obesity and dental caries through a dietary survey or additional investigations considering other confounding factors.